2002
DOI: 10.1093/brain/awf025
|View full text |Cite
|
Sign up to set email alerts
|

Brain atrophy in clinically early relapsing–remitting multiple sclerosis

Abstract: Brain atrophy measured by MRI is a potentially useful tool for monitoring disease progression in multiple sclerosis. The location, extent and mechanisms of brain atrophy in early disease are not well documented. Using quantitative MRI, this study investigated whole brain, grey and white matter atrophy in clinically early relapsing-remitting multiple sclerosis and its relationship to lesion measures. Data came from 27 normal control subjects (14 females and 13 males, mean age 36.1 years) and 26 subjects with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
317
5
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(343 citation statements)
references
References 49 publications
18
317
5
1
Order By: Relevance
“…We observed a significant negative correlation between mean cortical thickness and the total volume of WM lesions, confirming previous studies that used a volumetric approach (Ge et al, 2001;Chard et al, 2002;De Stefano et al, 2003). We found that the correlation between the TWMLL and cortical thickness was statistically significant at almost every vertex of the surface model after correcting for multiple comparisons.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We observed a significant negative correlation between mean cortical thickness and the total volume of WM lesions, confirming previous studies that used a volumetric approach (Ge et al, 2001;Chard et al, 2002;De Stefano et al, 2003). We found that the correlation between the TWMLL and cortical thickness was statistically significant at almost every vertex of the surface model after correcting for multiple comparisons.…”
Section: Discussionsupporting
confidence: 89%
“…However, it is also possible that these gray matter regions are somehow intrinsically more vulnerable to direct involvement by the disease; indeed, histopathological studies have demonstrated that the cingulate gyrus, temporal lobe, and insula generally show a higher prevalence of cortical demyelinated lesions than other areas (Bö et al, 2003;Vercellino et al, 2005;Kutzelnigg and Lassmann, 2006). Two studies on relatively small numbers (n = 30 and 26) of MS patients reported a correlation between fractional GM volume and total WM lesion volume, but not disability (Ge et al, 2001;Chard et al, 2002). However, another report in a larger patient group (n = 65) did uncover a correlation between GM volume and EDSS (De Stefano et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, neuroimaging studies revealed microglia activation with minimal inflammatory cell infiltrates in proximity of cortical axonal transections [19]; this gray matter abnormality occurs surprisingly early and correlates much better with permanent disability, demonstrating that microglia activation in gray matter correlates with neuron loss and MS onset ( [37,51,201,230]). …”
Section: The Eae Animal Modelmentioning
confidence: 99%